2013
DOI: 10.1002/adma.201302854
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Evidence of Morphological Degradation on a Nanometer Scale in Polymer Solar Cells

Abstract: In situ measurement of a polymer solar cell using micro grazing incidence small angle X-ray scattering (μGISAXS) and current-voltage tracking is demonstrated. While measuring electric characteristics under illumination, morphological changes are probed by μGISAXS. The X-ray beam (green) impinges on the photo active layer with a shallow angle and scatters on a 2d detector. Degradation is explained by the ongoing nanomorphological changes observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
212
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(224 citation statements)
references
References 27 publications
10
212
2
Order By: Relevance
“…11 For example, it has been shown that simply operating solar cells composed of blended materials generates enough heat to induce further phase separation and detrimentally increase domain sizes in semicrystalline materials. 12 This hinders application of these materials in industry where reproducibility and stability are crucial. In addition, a key advantage of OPV is the solution processability of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, it has been shown that simply operating solar cells composed of blended materials generates enough heat to induce further phase separation and detrimentally increase domain sizes in semicrystalline materials. 12 This hinders application of these materials in industry where reproducibility and stability are crucial. In addition, a key advantage of OPV is the solution processability of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…20 A thorough understanding of their growth and structure is prerequisite to the efficient implementation on a technological basis, since the morphology of OSCs has a strong impact on their charge carrier mobility and other physical properties. 1,[20][21][22][23][24][25][26][27][28][29][30] The basic understanding has largely remained on a qualitative level, since in most cases the film structure is not sufficiently well defined due to complex structural phenomena such as phase coexistence, changes in the molecular conformation or orientation, and morphological transitions. Thus there is the avid need to comprehend the different structural aspects of the hybrid structures like, e.g.…”
mentioning
confidence: 99%
“…Next-generation photolithography tools in the extreme UV-wavelength regime (EUV lithography) [4] and directed self-assembly of block copolymer (BCP) thin films [5][6][7][8][9][10] are promising techniques for producing a wide variety of structures with great accuracy and dimensions down to several nanometers [11,12]. Not only microelectronics, but also other emerging fields like organic photovoltaics [13,14], nanotemplating [15,16], or surface functionalization [17,18] make increasing use of structuring in the nanometer range by thin film deposition, processing, and self-assembly techniques.…”
Section: Introductionmentioning
confidence: 99%